How worker participation affects reciprocity under minimum remuneration policies: Experimental evidence - Katrin Köhler; Beatrice Pagel; Holger A. Rau (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2015)
We analyze the role of worker participation for the success of minimum remuneration policies. In our experiments employers remunerate workers doing a real-effort task. We vary the way how a minimum remuneration policy is introduced. In the worker-participation treatment, workers bargain with the employer on the enforcement of the policy. In the control treatment the policy is exogenously introduced. We find a pronounced effort increase after the policy was enforced. An exogenous introduction has detrimental effects, i.e., employers frequently pay a premium to maintain performance. Thus, worker participation may be an effective means for maintaining reciprocity under minimum remuneration policies.
Keywords: C91; J31; J33; M52; 330; bargaining; experiment; real effort; worker participation